Coping Mechanisms Utilized by Individuals With Drug Addiction in Overcoming Challenges During the Recovery Process: A Qualitative Meta-synthesis - Agus Setiawan; Junaiti Sahar; Budi Santoso; Muchtaruddin Mansyur; Syamikar Baridwan Syamsir (Korean Society for Preventive Medicine, 2024)
Objectives: Recovery from drug addiction often poses challenges for the recovering person. The coping mechanisms employed by these individuals to resist temptations and manage stress play a key role in the healing process. This study was conducted to explore the coping strategies or techniques that individuals with addiction use to handle stress and temptation while undergoing treatment. Methods: A qualitative meta-synthesis approach was utilized to critically evaluate relevant qualitative research. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines were used for article selection, with these standards applied to 4 academic databases: Scopus, PubMed, ProQuest, and CINAHL. The present review included studies published between 2014 and 2023, selected based on pre-established inclusion criteria. The quality of the studies was assessed using the Critical Appraisal Skills Programme Qualitative Studies Checklist. This review was registered with the International Prospective Register of Systematic Reviews (PROSPERO) under the registration number CRD42024497789. Results: The analysis of 13 qualifying qualitative articles revealed 5 major themes illustrating the coping mechanisms employed in the pursuit of recovery by individuals who use drugs. These themes include seeking social support, as well as psychological coping strategies, spiritual experiences, professional interventions, and the enhancement of awareness. Conclusions: Among individuals with drug addiction, coping mechanisms are crucial for resisting stress and temptations throughout the recovery process. Healthcare professionals, as medical specialists, can establish more thorough and effective plans to support these patients on their path to recovery.